Patient Experience (PX) Giants: Pioneers and the Path Forward - Geoffrey Silvera; Courtney Haun; Varun Natarajan (Patient Experience Journal)
This commentary pays tribute to the foundational figures in patient experience (PX) scholarship, acknowledging the "PX Giants" whose contributions have established and expanded the field's core principles. Building upon the analysis in Foundational PX, which identified highly cited works, this piece honors individual contributors who have contributed to the scholarly foundation of PX. It highlights the cumulative impact of both frequently cited and consistently productive scholars, underscoring their essential role in shaping patient-centered care. PX Giants have pioneered frameworks on diverse aspects of PX, such as patient-provider communication, care disparities, and the integration of patient perspectives into quality assessments. Through global collaborations, novel measurement tools, and strategic insights, these leaders have elevated PX as a central healthcare priority. Looking forward, the commentary emphasizes the need for emerging PX leaders to address complex challenges, including workforce shortages, technological advancements, and political and economic pressures. The digital transformation in healthcare, while promising improved access and personalization, poses potential risks to patient-centeredness, necessitating vigilance in maintaining empathetic, human-centered care. Additionally, ensuring equitable PX across fragmented systems requires culturally competent and accessible care models. Through cross-disciplinary collaboration and continued advocacy, the next generation of PX scholars and practitioners will advance this vital work, adapting PX to meet the needs of diverse patient populations and evolving healthcare landscapes.